High-accuracy Three-dimensional Measurement by Improving the Asymmetry of Dithered Patterns. (May 2019) - Ting, Wang; Bin, Lin; Wanzhen, Zhang; Bo, Chen
Abstract: The previously proposed dithering defocusing technology performs well for threedimensional (3D) measurement when stripes are relatively wide, yet suffers if stripes are narrow. This paper finds two asymmetries in dithered patterns generated by the Sierra Lite dithering algorithm and verifies the longitudinal fringes are more advantageous for phase-shifting technique over transverse fringes. Furthermore, this paper proposes an algorithm with a meandering scan. In each pattern, the pixels of odd lines are scanned from left to right while the even lines are scanned from right to left. The proposed method avoids the quantization errors propagating in a specific direction and greatly improves the symmetry of longitudinal fringes. Both simulation and experimental results have shown this method can effectively improve accuracy of 3D measurement especially for narrow stripes.